(3eLehYI GdUdhGJ GdfHhjIs - (3eMeO WjH GdGSeGA Hf CMeO Hf eMeO WjH GdGSeGA GdbGOQj GdSeGfj GdeGdcj,J (B1354 (3g` s
(3ChdgG (B:s
(3CYhP HGddg ef GdTjWGf GdQLje HSe Gddg GdQMef GdQMje (B" (3Ef Gddg hedGFcJg jUdhf YdiGdfHi jG CjgG GdPjf BefhG UdhG Ydjg hSdehG JSdjekG s
(3BNQgG (B:s
(3eG bGe OGY GdEdg HLGgce Ch SQ edgha HSQYI fLOI Ch bGd QGLi ajVce eSJLOjkG jG SjO GdQSd GdcQGe GdNjQI Gddge Ud Ydi SjOfG eMeO GdaGJM GdNGJe Pi GdeLO GdCSfi hGdfYhJ GdMSfi hGdZjV GdCgfi hYdi Bdg hUMHg hSde s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdShOGf (B_ (3jhfSch s
Keywords: (3GdJUha hGdBOGH GdTQYjIs